The Inactivation of Microscopic Fungi in Bakery Products Using Hurdle Technology—A Case Study - Anna Diowksz; Przemysław Kopeć; Anna Koziróg (Applied Sciences)
The issue of the microbiological spoilage of bakery products with an extended shelf life declared by the producer was the reason for searching for an effective solution. The aim of the investigation was to find the sources of infection, identify microorganisms causing product spoilage, and propose ways to eliminate the problem without the use of chemical preservatives in the product. It was found that the dominant contaminating microorganisms are yeasts of the genus Hyphopichia sp., Saccharomyces sp., and Candida spp., as well as molds—Aspergillus spp. and Penicillium spp. The microbiological quality of the production environment was assessed, and as a remedial action, a disinfection process was carried out. The influence of gas composition in MAP (modified atmosphere packaging) and the use of ethanol during packaging on the incidence of yeast or mold occurrence was checked. The effectiveness of using sourdough was also tested. The best results were achieved by using sourdough obtained with selected starter cultures and using a gas mixture for packaging in the proportion of 70% carbon dioxide and 30% nitrogen, without the addition of ethanol. These conditions ensured the expected shelf life of bakery products while maintaining their quality.